Instructions to Authors - Editor, The (Indian Journal of Pharmacy Practice)
Indian Journal of Pharmacy Practice (ijopp) is official journal of Association of Pharmaceutical Teachers of India (APTI). Indian Journal of Pharmacy Practice, a quarterly publication is devoted to publishing reviews and research articles in the area of Pharmacy Practice. Articles in the areas of clinical pharmacy, hospital pharmacy, community pharmacy, p h a r m a c e u t i c a l c a r e , p h a r m a c o v i g i l a n c e , pharmacoeconomics, clinical research, clinical pharmacokinetics and other related issues can be sent for publication in ijopp. All manuscripts should be submitted in triplicate along with 'Authorship Responsibility Undertaking', signed by all the authors of the paper to,